MANIFESTATION OF QUANTITATIVEITY IN SPEECH STYLES (ResearchJet Journal of Analysis and Inventions, 2021)
This article is devoted to the expression of quantitative words in different speech situations. It is also explained that quantitativeity applies to all levels. Quantifiers also mean expressiveness.